2023
DOI: 10.3390/ma16072757
|View full text |Cite
|
Sign up to set email alerts
|

Laser Powder Bed Fusion of Dissimilar Metal Materials: A Review

Abstract: The laser powder bed fusion (LPBF) technique is used to manufacture complex and customised components by exploiting the unique advantages of two types of metal materials to meet specific performance requirements. A comprehensive overview of LPBF-processed dissimilar metal materials, a combination of different single metals or alloys, is developed. The microstructure in the fusion zone and the corresponding mechanical properties of LPBF-processed dissimilar metal materials are summarised. The influence of proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 177 publications
0
4
0
Order By: Relevance
“…A wide range of materials can be produced additively using SLM, and the mechanical properties of the component can be modified by adjusting their process parameters. The impact of different material qualities on the printability of the multimetal 3D-printing processes were examined by Hasanov et al and Guan et al [ 16 , 17 ]. On the basis of a predetermined process setting and scanning tactics, Chen et al explored the fabrication of 316L/CuSn10 bimetallic structures printed via SLM.…”
Section: Multimetal Additive Manufacturing Techniquesmentioning
confidence: 99%
“…A wide range of materials can be produced additively using SLM, and the mechanical properties of the component can be modified by adjusting their process parameters. The impact of different material qualities on the printability of the multimetal 3D-printing processes were examined by Hasanov et al and Guan et al [ 16 , 17 ]. On the basis of a predetermined process setting and scanning tactics, Chen et al explored the fabrication of 316L/CuSn10 bimetallic structures printed via SLM.…”
Section: Multimetal Additive Manufacturing Techniquesmentioning
confidence: 99%
“…Article [86] analyzes a non-oriented sheet with a thickness of 0.5 mm. The density of losses in the core is approximated by the relationship (19), where it was assumed that cutting affects only hysteresis losses.…”
Section: Simulation Models Of Changes In Electromagnetic Properties C...mentioning
confidence: 99%
“…As a result of their use, the destruction of the material's internal structure, resulting from the implementation of the mechanical or laser cutting process (manifested by the deterioration of the material's magnetic properties), is avoided. Referring to additive manufacturing methods, a group of works describing research conducted on sintered materials can be identified [8][9][10][11][12][13][14][15], as well as a group of works depicting the research results using laser powder bed fusion technology [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of some recently introduced multi‐material powder bed systems, [ 25–27 ] most powder bed processes have uniform feedstock and do not allow compositional grading. Thus, the only possible route in LPBF to control microstructural evolution is by local tailoring of the processing parameters.…”
Section: Introductionmentioning
confidence: 99%